Proses Kebijakan di Daerah: Formulasi Peraturan Daerah Provinsi Riau tentang Pengelolaan Daerah Aliran Sungai - Reski Lestari; Riant Nugroho; Syed Agung Afandi (LPPM Universitas Abdurrab, 2021)
The decline in watershed conditions in Indonesia was marked by an increase in landslides, erosion and sedimentation, flooding, and drought. Each watershed has its own problems, so that in watershed management, special rules are needed to regulate problems in the watershed. The management of the Riau Province watershed requires specific regulations governing the Riau Province watershed in accordance with the clarification of the watershed. In this case, an initiative draft of the DPRD Commission B appeared in the management of watersheds in Riau Province. This article uses a qualitative approach with descriptive analysis methods, data collection is done by interview, observation and documentation. The results showed that in the formulation of the Riau Province Regional Regulation on Watershed Management, there were several processes and stages, namely the formulation of problems, the policy agenda, the selection of alternative policies to solve problems, and finally the stage of determining the policy. From the formulation process that was carried out, the initial draft with the draft after the Plenary Meeting that had been carried out did not experience significant changes, the changes only revolved around adding concepts in watershed management which were embodied in the Regional Regulation Draft.